PERBEDAAN PENYULUHAN MEDIA DENTAL BRAILLE EDUCATION (DBE) DAN DENTAL AUDIO EDUCATION (DAE) TERHADAP PENGETAHUAN ORAL HYGIENE PADA PENYANDANG TUNANETRA DI SDLB A PAJAJARAN BANDUNG - Aprilianty, Windy Marsella; Nurjanah, Neneng; Utami, Ulfah; Fatimah, Siti (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Palembang, 2024)
Background: The limitations of blind children are one of the obstacles to gaining knowledge about dental and oral hygiene. Blind children need appropriate media to increase their knowledge of dental and oral hygiene. One of them uses braille and audio. The aim of this research is to determine the difference between dental braille education (DBE) and dental audio education (DAE) on oral hygiene knowledge for blind people at SDLB A Pajajaran Bandung. Methods: This research method uses a quasi-experiment with a one group pretest posttest design. Sampling was carried out using a proportional sampling technique so that the number of respondents was 50 students. The data analysis technique uses the Wilcoxon test to determine the effect of each media group and the Mann Whitney test to determine the differences between the two media groups. Results: The research results showed that there was a significant difference in the level of knowledge with a value of p=0.000 (p<0.05) in counseling on dental braille education (DBE) and dental audio education (DAE) media. Conclusion: It can be concluded that counseling using dental audio education (DAE) media is more effective in increasing knowledge of dental and oral hygiene than dental braille education (DBE) media.